Ultrahigh-energy cosmic ray hotspots from tidal disruption events. Issue 3 (23rd December 2016) - Pfeffer, Daniel N.; Kovetz, Ely D.; Kamionkowski, Marc
Abstract: We consider the possibility that tidal disruption events (TDEs) caused by supermassive black holes (SMBHs) in nearby galaxies can account for the ultrahigh-energy cosmic ray (UHECR) hotspot reported recently by the Telescope Array (TA) and the warm spot by Pierre Auger Observatory. We describe the expected cosmic ray signal from a TDE and derive the constraints set by the time-scale for dispersion due to Galactic and intergalactic magnetic fields and the accretion time of the SMBH. We find that TDEs in M82 can explain the hotspot detected by the TA regardless of whether the UHECRs are composed of protons or heavier nuclei. We then check for consistency of the hot and warm spots from M82 and Cen A with the full-sky isotropic signal from all SMBHs within the Greisen-Zatsepin-Kuzmin (GZK) radius. This analysis applies to any scenario in which the hot/warm spots are real and due to M82 and Cen A, regardless of whether TDEs are the source of UHECRs. We find that the isotropic flux implied by the luminosity density inferred from M82 and Cen A is bigger than that observed by roughly an order of magnitude, but we provide several possible explanations, including the possibility of a local overdensity and the possibility of intermediate-mass nuclei in UHECRs, to resolve the tension.